MENGEMBANGKAN KREATIVITAS KEKARYAAN TARI BAGI SISWA SMA - Dwi Wahyudiarto; Dwi Rahmani; Dwi Maryani (Abdi Seni, 2020)
The community services (Pengabdian Kepada Masyarakat) is implemented at SMA Batik I Surakarta with the theme “Dance for expression, actualization and recreation”. This training is more focused on training and preparation work for strengthening creativity of dance for high school students. This dance training will encourage students to develop creativity, improved their ability in dancing techniques, and will master the dance material. Besides the experience of affective, cognitive and psychomotor exercises done in the process, it is also useful in building character of students.Specifically, dance training activities with three methods: the first method is focus group discussion; secondly, method of creative shapes, and thirdly, drill method. Focus group discussion is done for giving reinforcement insight / knowledge regarding the values of art and humanitarian into in life experience learners. Experimental methods are supposed to develop, to enhance students' skills in the creative process, and to drill method in providing reinforcement in its training of dancing physical abilities.Training program is conducted over six months, it also involves the accompanying direct chaperone teacher from school. This is a very important role in the smooth running drills, and also for the sustainability of the program. Materials and training results are in the form of a dance piece entitled Tembang Nusantara. A dance piece is worked out based on the pattern of the song rhythm or songs of Indonesian region. This theme is chosen because basically, the song has a very good meaning for teenager education. Orchestral colors which work on the musical form is very handsome, spirit, agile, aggressive so it is appropriate for high school age. Results of the training can be arranged including new material in filmed dance, build confidence for students primarily through roles or characters. In addition, this program also can make it dynamic and develop the spirit of art, as well as the growing appreciation for all the students in SMA Batik I Surakarta.   Keywords: Training, creativity, Students.